A kárpát-medencei államosodási térfolyamatok kérdőjelei: széttagolódás, kárpát-medencei integráció, avagy beolvadás az euro-atlanti nagytérségi rendszerekbe? - Hajdú, Zoltán (Közép-Európai Közlemények, 2008)
The study surveys the historical and modern state-bilding processes of the Carpathian Basin. The paper is focusing on the connections between the Carpathian Basin as a physical geographical unit and the long term historical-territorial processes. Between 1867–1918 the Historical Hungary was nearly owerlaping the Carpathian Basin, In 1920 the territory of the Carpathian Basin was divided between five countries. After 1945 the whole territory of the Carpathian Basin turned to be under Soviet military rule. At the biginning of the transitional period (from the Socialism to Capitalism) the Soviet Union collapsed, Csechoslovakia and Yugoslavia were divided into new states. The Carpatian Basin is divided between eight sates,and at the same time most of the countris would like to be NATO and EU members.